The Effect Of Competence, Organizational Cultur And Interpersonal Communication On Employee Performance At Pt. Erajaya Bengkulu City - Esty Wulandari; Ida Anggriani; Tri Febrina Melinda (Universitas Dehasen Bengkulu, 2026)
Employee performance plays a crucial role in determining the success of a company. Performance improvement is not only influenced by individual abilities but also by the work environment, organizational culture, and patterns of interpersonal communication among employees. In the context of PT. Erajaya Bengkulu City, it is important to understand the extent to which competence, organizational culture, and interpersonal communication contribute to achieving optimal employee performance. Issues such as differences in employee competence levels and less effective communication at work serve as the basis for this research. This study aims to determine the effect of competence, organizational culture, and interpersonal communication on employee performance at PT. Erajaya Bengkulu City, both partially and simultaneously. The study employed a quantitative approach with an associative method. The population consisted of 100 employees of PT. Erajaya Bengkulu City, with a saturated sampling technique. Data were collected using questionnaires and analyzed through multiple linear regression to examine the relationships among variables. The results indicate that competence, organizational culture, and interpersonal communication have a positive and significant effect on employee performance, both partially and simultaneously. The coefficient of determination (R²) value of 0.840 shows that these three variables contribute 84% to changes in employee performance, while the remaining 16% is influenced by other factors outside this study. Therefore, the higher the competence, the stronger the organizational culture, and the more effective the interpersonal communication, the better the employee performance at PT. Erajaya Bengkulu City.